Estimation of optoacoustic contrast agent concentration with self-calibration blind logarithmic unmixing - Dean-Ben, X. Luis; Buehler, Andreas; Razansky, Daniel; Ntziachristos, Vasilis (Physics in Medicine and Biology, 2014)
Chromophore quantification in optoacoustic tomography is challenging due to signal contributions from strongly absorbing background tissue chromophores and the depth-dependent light attenuation. Herein we present a procedure capable of correcting for wavelength-dependent light fluence variations using a logarithmic representation of the images taken at different wavelengths assisted with a blind unmixing approach. It is shown that the serial expansion of the logarithm of an optoacoustic image contains a term representing the ratio between absorption of the probe of interest and other background components. Under assumptions of tissue-like background absorption variations, this term can be readily isolated with an unmixing algorithm, attaining quantitative maps of photo-absorbing agent distribution. © 2014 Institute of Physics and Engineering in Medicine.
CRIS-Team Scopus Importer:2023-03-08
Keywords: multispectral unmixing; optoacoustic probes; optoacoustic tomography; quantitative imaging